Analysis on the changes of fertilization intensity and efficiency in China's grain production from 1980 to 2019. (23rd September 2022) - Liu, Qinpu; Wu, Ta Yeong; Tu, Wei; Pu, Lijie
Abstract: BACKGROUND: Relieving serious non‐point source pollution of nitrogen (N), phosphorus (P), and potassium (K) is an urgent task in China. It is necessary to explore the changing characteristics of chemical fertilization intensity (FI) and efficiency to provide references. A new method of 'relative productivity proportion weight', which was simpler than data envelope analysis, was proposed to construct models of fertilizer allocation efficiency (FAE) and chemical fertilizer integrated efficiency (FIE) by considering NPK multi‐inputs and the grain output scale, respectively. RESULTS: During 1980–2014, the FIs of NPK chemical fertilizers in China showed a significant growing trend. After reaching the highest value of 339 kg ha −1 in 2014, FIs were reduced to 303 kg ha −1 in 2019, higher than the 225 kg ha −1 maximum safe usage internationally recognized. Meanwhile, the pattern of change of FAE was one of 'decreasing to increasing', with values of 1 in 1980, 0.66 in 2003, and 0.80 in 2019. FIE basically showed an increasing trend, which could be divided into three stages: the first stage of low efficiency during 1980–2009, the second stage of medium efficiency after 2010, and the third stage of high efficiency after 2018. CONCLUSION: From 1980 until 2019, a reduction of FAE from 1 to 0.80 with an average of 0.75 was observed in China. FIE was found between 0.65 and 0.85 and had the potential of upgrading by 15–35%. Therefore, China needs to improve the fertilizer use efficiency in order to strive for negative growth of chemical fertilizer intensity and ecological agriculture construction. © 2022 Society of Chemical Industry.